The Pine Branch, October 1928 - (:unkn) unknown (Valdosta, Ga. : Writers Club of the Georgia State Womans College., 1928)
The Pine Branch, October 1928. Periodical magazine. Created and published by the Writers Club of the Georgia State Womans College, Valdosta, Georgia, 1928. Includes: editorials, photographs, poems, short stories, and other writings.
Trees: M K Burrows 3 | `Tis the Fad My Lad: B Young 4 | How Lyrics Began: M K Burrows 7 | Evening Sea: -L Nix 8 | On Being Prepared: D Harper 1 9 | Jane Plays the Game: I Spooner 11 | Editorials 16 | Y W C A Notes 18 | Athletic News 20 | Society News 21 | Alumnae News 23 | Local News 26 | Jokes 28
Keywords: College publications; College student newspapers and periodicals; Valdosta State University--Periodicals; Women; Women's colleges--Georgia--Valdosta; Georgia State Womans College; Valdosta; Schools--Georgia; Education